421 Psychiatric and social outcomes following pediatric concussion: a population-based study. (20th November 2022) - Russell, Kelly; Walld, Randy; Bolton, James; Chateau, Daniel; Ellis, Michael
Abstract : Background: There has been increased attention on the long-term effects of concussion. The objective was to examine youth who have or have not sustained a concussion to determine the risk of adverse psychosocial outcomes. Methods: A retrospective population-based analysis was conducted among Manitoba youth (10–18 years) between 2000–2005. Using provincial administrative health data, concussion cases were identified and matched by age and neighborhood to randomly selected non-concussion controls. Youth were followed for 10–15 years. New onset psychiatric, social, and judicial outcomes were extracted using linked administrative datasets. Adjusted hazard ratios with 95% confidence intervals were calculated. Results: There were 2082 concussed youth matched to 10, 510 non-concussed youth. Concussed youth had an increased risk of any psychiatric disorder (HR: 1.34; 95% CI: 1.25, 1.45), mood disorder (HR: 1.30; 95% CI: 1.18, 1.43), psychosis (HR: 1.43; 95% CI: 1.18, 1.74), substance abuse disorder (HR: 1.67; 95% CI: 1.31, 2.14), and receiving a psychotropic prescription (HR: 1.31; 95% CI: 1.20, 1.42). Girls had an increased risk of ADHD following concussion (HR: 1.89; 95% CI: 1.17, 3.05). Concussed youth had an increased risk of being accused (HR: 1.22; 95% CI: 1.11, 1.34), victim (HR: 1.29; 95% CI: 1.11, 1.48), or witness (HR: 1.16; 95% CI: 1.01, 1.32) of a crime or having contact with Child and Family Services (HR: 1.33; 95% CI: 1.10, 1.62). There was no association between concussion and risk of attempting or completing suicide, receiving housing support, or income support. Conclusions: Concussion was associated with an increased risk for several adverse psychosocial outcomes. Identifying risk factors for adverse psychosocial outcomes would assist in intervention development. Learning Outcomes: Concussion prevention efforts need to be maximized to prevent long-term adverse outcomes.